Minimum Competency Assessment in Madrasah Ibtidayah - Jannah, Raihanatul; Khairunnisa; Sholeh, Makherus; Khaliq, Restu (LETIGES, 2024)
This study aims to analyze the implementation of the Minimum Competency Assessment (MCA) at the Madrasah Ibtidaiyah level. To examine the assessment's preparation, implementation, and understanding among educators and strategies to develop literacy and numeracy within the assessment framework. This study used a qualitative approach, involving 24 subjects selected through stratified sampling based on school status and role, including principals, teachers, supervisors, and students. Data were collected through interviews, observations, and documentation. Data analysis followed the stages of Milles and Huberman, including data condensation, data display, and conclusion. The results showed that the preparation of the MCA included preparing facilities, improving internet connectivity, and training for teachers. The MCA was carried out by dividing students into several waves and sessions, including simulations before the assessment began. However, there needs to be more teachers' understanding of the objectives of the MCA, especially in terms of literacy and numeracy, which affects the overall effectiveness of the assessment. Strategies to develop literacy and numeracy, such as integrating technology into teaching practices, are essential to better prepare students for the digital aspects of the evaluation. In addition, the findings show that despite significant efforts made by schools to prepare for MCA, challenges such as inadequate technological resources, limited teacher preparedness, and technical issues during assessments pose substantial barriers. The study suggests that addressing these challenges is critical to improving the effectiveness of MCA and achieving its goals of improving student competency and overall educational quality.